Second-best Congestion Pricing Schemes in the Monocentric City - Erik T. Verhoef (Tinbergen Institute, 2004)
Paper submission from Erik Verhoef (everhoef@econ.vu.nl)Discussion Paper Submission Form - STEP 1This discussion paper abstract is submitted by Erik Verhoef (everhoef@econ.vu.nl)Template-Type: ReDIF-Paper 1.0Series: Tinbergen Institute Discussion PapersCreation-Date: Number: Author-Name: Erik T VerhoefAuthor-Email: everhoef@econ.vu.nlAuthor-Workplace-Name: VUTitle: SECOND-BEST CONGESTION PRICING SCHEMES IN THE MONOCENTRIC CITYAbstract:This paper considers second-best congestion pricing in the monocentric city, with endogenous residential density and endogenous labour supply. A spatial general equilibrium model is developed that allows consideration of the three-way interactions between urban density, traffic congestion and labour supply. Congestion pricing schemes are analyzed that are second-best `by design' (and not because distortions exist elsewhere in the spatial economy), like cordon charging and flat kilometre charges. Both for Cobb-Douglas utility and for CES utility, the analyses suggest that the relative welfare losses from second-best pricing, compared to first-best pricing, are surprisingly small.
Keywords: R41; R48; D62; 330; Traffic congestion; second-best pricing; urban structure; spatial general equilibrium; Verkehrsstau; Straßenbenutzungsgebühr; Second Best; Theorie